Innovation Learning: Audio Visual and Outdoor Study to Enhance Student’s Understanding of Disaster - Furqan, M. Hafizul; Maryani, Enok; Ruhimat, Mamat (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
Education is functioned to prepare human to compete in overcoming various challenges. One of challenge faced by Indonesian nation is natural disaster. The effective method to reduce the risk of natural disaster (disaster mitigation) is by enhancing understanding of disaster in each individual. Aceh Tsunami Museum (ATM) is one of important site which is build to remember the big disaster event which happened in 2004 in Aceh and as disaster learning source. This study is aimed to find out the influence of ATM utilization in enhancing students’ understanding of disaster, by using outdoor study method (visit ATM) and audio visual media (Film with disaster themed). The research design is Experimental quasi. Sample of this study are students of class X-2 IS and X-3 IS with total of 57 students. Data is obtained from literature study, observation, test, questionnaire, and documentary study. The result showed that utilizing ATM by outdoor study method can better enhance understanding of disaster compared to audio visual media. Constructivism learning approach can create more meaningful learning. Teachers are suggested to apply constructivism learning approach in learning process.